2016
DOI: 10.1080/23794925.2016.1227949
|View full text |Cite
|
Sign up to set email alerts
|

Child Trauma Exposure and Posttraumatic Stress Disorder: Identification in Community Mental Health Clinics

Abstract: We examined the identification of trauma exposure and post-traumatic stress disorder (PTSD) in help-seeking urban children (N=157) presenting for care in community mental health clinics. Children and their parents completed a standard intake assessment conducted by a community clinician followed by a structured trauma-focused assessment conducted by a study clinician. Clinicians provided ratings of child functional impairment, parents reported on internalizing/externalizing problems, and children provided self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This study's finding of comparable long-term treatment response regardless of trauma history has important implications for adolescents, their families, and their health care providers. As other studies have found comparable rates of trauma histories among help-seeking adolescents as the 53% in our sample (Chemtob et al, 2016;Lau & Weisz, 2003), considering trauma history when selecting and developing treatment may be a concern for about half the youth seeking mental health treatment. Choice of treatment, sense of autonomy, and feelings of normalcy are important for depressed adolescents and their families (Wisdom, Clarke, & Green, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…This study's finding of comparable long-term treatment response regardless of trauma history has important implications for adolescents, their families, and their health care providers. As other studies have found comparable rates of trauma histories among help-seeking adolescents as the 53% in our sample (Chemtob et al, 2016;Lau & Weisz, 2003), considering trauma history when selecting and developing treatment may be a concern for about half the youth seeking mental health treatment. Choice of treatment, sense of autonomy, and feelings of normalcy are important for depressed adolescents and their families (Wisdom, Clarke, & Green, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…Although a thorough assessment of childhood trauma and loss is indispensable to implementing trauma-informed evidence-based practice, including case conceptualization, treatment planning, identification of intervention foci, prioritizing targets of intervention, selection of intervention strategies, and monitoring of treatment effects (see Layne, Steinberg, & Steinberg, 2014), many clinicians do not systematically screen for trauma exposure as an integral part of routine clinical intake. For example, Chemtob et al (unpublished manuscript) 2012 examined trauma assessment practices among clinicians working with children and adolescents and reported that, despite being required to specifically ask about exposure to physical abuse, sexual abuse, and domestic violence at intake, community-based clinicians reported substantially lower rates of trauma exposure than research study clinicians who interviewed the same children. Similar patterns have also been found for clinicians working with adult populations (Young, Read, Barker-Collo, & Harrison, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD can occur after the experience or witnessing of one or more Traumatic Events (TE) during childhood or adulthood [ 3 , 4 ]. Traumatic events can include physical, sexual or emotional abuse during childhood [ 5 , 6 ]. In adulthood these events include the experience or witnessing, of violent personal assault such as physical or sexual violence perpetrated by a partner, terrorism, serious illness or death of a loved one [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%